Estudo das estruturas atômicas de superfície dos isolantes topológicos Bi2Se3 e Bi2Te3, e de filmes finos de La0.7Sr0.3MnO3 - Diogo Duarte dos Reis (2014)
The physico-chemical, electrical, magnetic, and optical properties of a surface can be seen as a function of their electronic structure which is strongly related to its atomic structure. Furthermore, the creation of a surface represents a break in one direction of periodicity of the crystal, which can result in structural changes and consequently generates changes in the above mentioned properties. Thus it is of extremely significance the experimental determination of surface structure for a complete understanding of the properties of a material. In this thesis, the low-energy electrons diffraction technique (LEED) was applied to the investigation of the atomic structures of the (111) surfaces of two topological insulators Bi2Se3 and Bi2Te3, and also to study the crystallographic structure evolution with the thickness of doped manganate thin films La0:7Sr0:3MnO3 grown on a SrTiO3 as a substrate. The results for Bi2Te3 and Bi2Se3 show that these surfaces undergo slight relaxations, being almost bulk terminated. Among the details researched is the value of the van der Waals gap, due to assumptions about its influence on the electronic structure of these materials. The structural investigation of La0:7Sr0:3MnO3 thin films was carried out during the internship at the Department of Astronomy and Physics, Louisiana State University, United States of America, under the supervision of Prof. Ward Plummer. This study showed that the surface undergoes stoichiometric and also structural changes in relation to the bulk. Special attention was paid to the evolution of the bond angle O-Mn-O, representing a Jahn-Teller distortion as well the tolerance factor, which has a minimum value when the thickness reaches the critical value wherein the metal-insulator transition occurs.